Partisipasi Masyarakat di Sekitar Sekolah Dalam Pembentukan Karakter Gotong Royong Siswa di SDNegeri 01 Kandis - Wahyu Adi Pratama; Magdad Hatim; Nyiayu Fahrizah Fuadiah (Departement of Mathematics Education, 2024)
In improving children's character, it is not only focused on government but also the needs of society. Society is one of the most important parts in the process of forming children's character, especially in the school environment. In this way, the researcher analyzes community participation in improving the mutual cooperation character of class I students. The formulation of the problem in this research is